IDENTIFICATION OF CONFIDENCE OF PROSPECTIVE MATHEMATICS TEACHERS IN COMPLETING PRESENTATION TASKS - Supriyo (Sean Institute, 2022)
This study aims to determine the self-confidence of prospective mathematics teachers in completing presentation assignments with the help of Prezi media and the factors that influence it. This research is a qualitative research. The subjects of this study were student teacher candidates at the Mathematics Education of PGRI Wiranegara University who took the Capita Selecta Mathematics course in elementary school. The research data were obtained through observation, questionnaires and interviews. Based on the results of the study showed that: (1) the confidence of prospective mathematics teachers in completing presentation assignments with Prezi media as a whole was 79.3% including the good category, (2) the factors that influenced self-confidence were: a) academic demands, b) self-esteem, c) surrounding social support, d) material readiness during presentations, e) self-appearance, f) material difficulties, g) short completion time, h) lack of experience in using Prezi media, i) weaknesses and strengths of Prezi.